2020
DOI: 10.3174/ajnr.a6808
|View full text |Cite|
|
Sign up to set email alerts
|

Secondary Otalgia: Referred Pain Pathways and Pathologies

Abstract: Otalgia is very common, and when the cause of ear pain is not identified on otoscopy and physical examination, cross-sectional imaging is routinely used to evaluate for potential sources of referred ear pain (secondary otalgia). Innervation of the ear structures is complex, involving multiple upper cervical, lower cranial, and peripheral nerves, which transit and innervate a large anatomic territory involving the brain, spine, skull base, aerodigestive tract, salivary glands, paranasal sinuses, face, orbits, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Convergence is believed to be a phenomenon in which a single second-order neuron receives nociceptive input from multiple sites, and the brain is unable to localize the correct primary stimulus [ 6 ]. It has been shown that migraine pain arises from the activation of meningeal perivascular afferents which are innervated by trigeminal nerve (CN V) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Convergence is believed to be a phenomenon in which a single second-order neuron receives nociceptive input from multiple sites, and the brain is unable to localize the correct primary stimulus [ 6 ]. It has been shown that migraine pain arises from the activation of meningeal perivascular afferents which are innervated by trigeminal nerve (CN V) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that migraine pain arises from the activation of meningeal perivascular afferents which are innervated by trigeminal nerve (CN V) [ 7 , 8 ]. The trigeminal nerve also gives off numerous branches throughout the ear including those that provide sensation to the anterosuperior pinna, external auditory canal and the lateral tympanic membrane [ 6 ]. This viscerosomatic convergence of meningeal and extracranial cutaneous afferents can explain the extracranial symptoms of migraine such as allodynia in the territory of trigeminal nerve [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] The earliest clinical or radiological signs of postoperative ICR (pICR) with occlusal disturbance or condylar resorption can occur 6 months after surgery; however, pICR is often observed instead at 1 or 2 years after surgery in most patients 4,[6][7][8][9][10][11][12] and ultimately leads to long-term relapse with decreased posterior facial height, progressive mandibular retrusion, and anterior open bite. [5][6][7][8][9][10][11][12][13][14][15][16][17] The pathophysiology of pICR is still not well understood. The main risk factors are suggested to be sex hormones and mechanical overloading on TMJ after orthodontic treatment, orthognathic surgery, trauma, internal derangement, occlusal therapy, or parafunctional habits.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary otalgia arises from pathology outside the ear, such as trigeminal neuralgia, auriculotemporal neuralgia, major auricular neuralgia, median neuralgia, and geniculate ganglion pain. 14,15 An otologic examination should be performed first to confirm whether it is primary ear pain. Cranial nerve examination is considered if the primary disease has been excluded.…”
Section: Anatomy and Possible Mechanism Of Glossopharyngeal Neuralgia...mentioning
confidence: 99%
“…Earache, medically termed as otalgia, is the most common symptom among the patients presenting in ENT OPD. Usually the pathology is within ear, called otogenic, but it become mysterious when there is no pathological findings in the ear and the site is other than the ear, referred non-otogenic [1]. The otalgia due to nonotogenic cause is also known as "referred otalgia".…”
Section: Introductionmentioning
confidence: 99%